E0424 Protective effect of trimetasidine on recurrent angina and MACE after percutaneous coronary intervention. (17th November 2010) - Xu, Xiao-Han; Zhang, Wei-Jun
Abstract : Objective: To evaluate the effect of pre-procedural acute oral administration of trimetazidine (TMZ) on percutaneous coronary intervention (PCI)-induced myocardial injury, and the effect of TMZ on prevention of recurrent angina and major adverse cardiac events (MACE) after PCI. Design: 200 patients with unstable angina pectoris undergoing PCI were prospectively randomised and randomly assigned to 2 groups. INTERVENTIONS: Patients were randomly assigned to receive or not an acute loading dose of 60 mg of TMZ prior to intervention and an ordinary dose of 20 mg Tid of TMZ after PCI. Cardiac troponin Ic (cTnI) levels were measured before and after PCI. Patients were followed up for 1 year. Main outcome: The total amount of cTnI released after PCI was significantly reduced in the TMZ group. Recurrent angina and MACE after PCI were significantly reduced in the TMZ group. Conclusion: Pre-procedural acute oral TMZ administration significantly reduces PCI-induced myocardial injury. Constituent use of TMZ could prevent recurrent angina and MACE after PCI.